Odpowiedź:
[tex]a)\\\\2(x-1)+3x=4-(2-2x)\\\\2x-2+3x=4-2+2x\\\\5x-2=2+2x\\\\5x-2x=2+2\\\\3x=4\ \ |:3\\\\x=\frac{4}{3}\\\\x=1\frac{1}{3}\\\\\\b)\\\\1-\frac{x-2}{6}=-x+\frac{3(x-1)}{4}\\\\1-\frac{x-2}{6}=-x+\frac{3x-3}{4}\ \ |\cdot12\\\\12-2(x-2)=-12x+3(3x-3)\\\\12-2x+4=-12x+9x-9\\\\16-2x=-3x-9\\\\-2x+3x=-9-16\\\\x=-25[/tex]
[tex]c)\\\\2(x-1)(2x+3)=4x^2+5x-6\\\\(2x-2)(2x+3)=4x^2+5x-6\\\\4x^2+6x-4x-6=4x^2+5x-6\\\\4x^2+2x-4x^2-5x=-6+6\\\\2x-5x=0\\\\-3x=0\ \ |:(-3)\\\\x=0\\\\\\d)\\\\3(2x-2)-4=-6(4-x)+14\\\\6x-6-4=-24+6x+14\\\\6x-10=-10+6x\\\\6x-6x=-10+10\\\\0=0\\\\R\'ownanie\ \ to\.zsamo\'sciowe\ \ ma\ \ niesko\'nczenie\ \ wiele\ \ rozwiaza\'n[/tex]